Organic co-solvents affect activity, stability and enantioselectivity of haloalkane dehalogenases - Stepankova, Veronika; Damborsky, Jiri; Chaloupkova, Radka (Biotechnology journal, 2013)
Haloalkane dehalogenases are microbial enzymes with a wide range of biotechnological applications, including biocatalysis. The use of organic co-solvents to solubilize their hydrophobic substrates is often necessary. In order to choose the most compatible co-solvent, the effects of 14 co-solvents on activity, stability and enantioselectivity of three model enzymes, DbjA, DhaA, and LinB, were evaluated. All co-solvents caused at high concentration loss of activity and conformational changes. The highest inactivation was induced by tetrahydrofuran, while more hydrophilic co-solvents, such as ethylene glycol and dimethyl sulfoxide, were better tolerated. The effects of co-solvents at low concentration were different for each enzyme-solvent pair. An increase in DbjA activity was induced by the majority of organic co-solvents tested, while activities of DhaA and LinB decreased at comparable concentrations of the same co-solvent. Moreover, a high increase of DbjA enantioselectivity was observed. Ethylene glycol and 1,4-dioxane were shown to have the most positive impact on the enantioselectivity. The favorable influence of these co-solvents on both activity and enantioselectivity makes DbjA suitable for biocatalytic applications. This study represents the first investigation of the effects of organic co-solvents on the biocatalytic performance of haloalkane dehalogenases and will pave the way for their broader use in industrial processes.
Keywords: Enzyme Stability; organické látky; vysoká teplota; bakteriální proteiny; Bacterial Proteins; cirkulární dichroismus; hydrolasy; Hot Temperature; Hydrolases; Recombinant Fusion Proteins; furany; rozpouštědla; stabilita enzymů; Organic Chemicals; Furans; Solvents; rekombinantní fúzní proteiny; Circular Dichroism